An inclusive spiritual education - Bellous, Joyce E. (International journal of children's spirituality, 2019)
I define human spirituality as a sense of felt connection, which is central to a human capacity to survive and thrive. That is, the spiritual lies at the foundation of human experience, so that everyone is spiritual, and typically, people use religious language to express spiritual concerns. In this paper, I lay out an inclusive approach to spiritual education that gets beneath religious and spiritual tensions to focus on human need. In offering the approach, and perhaps an attitude to the humanity of our learners, this essay describes four spiritual styles. Each one relies on a specific currency. The four currencies are, namely, word, emotion, symbol and action. I unpack the styles to show how, taken together, they create a holistic and humane literacy curriculum that welcomes children and youth into classroom experiences despite their personal religious differences or, perhaps, the indifference they bring with them to class.